Variation in nest placement by the European Greenfinch Chloris chloris in relation to the age of orange trees. Issue 1 (2nd January 2016) - Bensouilah, Taqiyeddine; Brahmia, Hafid; Zeraoula, Ali; Bouslama, Zihad; Houhamdi, Moussa
Abstract: Several studies have been performed to investigate the impact of tree characteristics on nest placement in canopy by nesting passerines. Although the breeding ecology of the European Greenfinch Chloris chloris was studied previously, the knowledge of its nest placement and nesting behavior is still scarce. This study aimed to examine the impact of the age of orange orchards Citrus sinensis on nest location within trees. During two consecutive breeding seasons (2013–2014), nest placement was studied in two different age categories of orange orchards in Guelma region, Northeast Algeria. The principal component analysis was performed to demonstrate the variability of nest placement with the age of orange plantation. Results indicated that nest placement in orange orchards is highly variable. The comparison of the two orchards with different age and structural characteristics revealed that nest placement in trees differed in all measured parameters. The Greenfinch nests are placed gradually higher and further from the main trunk as trees grow older. Although the relative vertical position of the nest rises with the age of trees, its relative horizontal position in the canopy does not change. These results demonstrate plasticity of this finch species in nest placement in orange plantations of this region.